Evaluation of the Implementation of the Adiwiyata Program in Elementary Schools in Grogol Petamburan District, Jakarta, Indonesia - Suprapto; Anah Suhaenah Suparno; Tri Isti Hartini (Community Medicine and Education Journal, 2023)
The Adiwiyata program is a movement carried out by school residents related to environmental care. This study aimed to obtain information related to the implementation of the Adiwiyata program in public elementary schools in the Grogol Petamburan District. The evaluation model used is CIPP, namely context, input, process, and product. This research method uses an evaluative approach. Scientific data were obtained through interviews, observations, and documentation, including documents on student learning outcomes. Interviews were conducted with school residents, namely school supervisors, principals, vice principals, teachers, the school Adiwiyata team, students, canteen traders, and parents or local residents. The results of the research on the implementation of the Adiwiyata program show that the component's context, the elementary school, has responded series this government policy by integrating various environmental issues in the vision, mission, school regulations, and in the implementation of the educational curriculum. On component input, the budget for the Adiwiyata program is available in the RKAS, the school's human resources include teachers and students, the facilities and infrastructure are adequate to support the Adiwiyata program, and it has a strategy to become an Adiwiyata school. In the components process, the school has gone through the stages of becoming an Adiwiyata school. Learning has been integrated with the Adiwiyata program and has a variety of concrete actions carried out by school members. Component product, there is the participation of students and school members to carry out real actions to preserve the environment. In conclusion, the implementation of the Adiwiyata program in elementary schools in Grogol Petamburan District, Jakarta, Indonesia, has been quite good, where systematic and coordinated efforts have been seen to realize the Adiwiyata program.